Analisis Visual Video Campaign Sport for Health Tentang Peran Olahraga Dalam Mendukung Kesehatan Mental - Ikhsan Nurfaisal; Inko Sakti Dewanto (Jurnal Riset Multidisiplin Edukasi, 2025)
Mental health often receives less attention, even though its role is as important as physical health. Although often considered trivial, mental health has a major impact on overall quality of life. One effective way to overcome mental health problems is to exercise, because when we exercise our bodies release hormones that can help reduce stress and improve mood. Because when we exercise there are many positive impacts, even the benefits of exercise when we are young can have an impact on the quality of our body in old age. Therefore, this research supports the role of video campaigns about sports on a person's mental health. Through visual analysis such as visual composition, color, typography or text, and graphic elements that strengthen the message in the video campaign that sport can affect mental health. It is hoped that through this video campaign, people will be more aware and understand the importance of exercise not only for physical health but also for mental health and as part of an overall lifestyle.